2008
DOI: 10.1590/s0103-21002008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Validação de conteúdo do diagnóstico de enfermagem conhecimento deficiente

Abstract: Objective: Perform content validation of the defining characteristics of the "deficient knowledge" diagnosis regarding coronary disease and myocardial revascularization. Methods: Fehring's Content Validation Model was used in this research. Fifty nurses took part in the students, all of them experts in Nursing Diagnosis, Cardiology and/or Educational Sciences. Results: The defining characteristics considered most important were: verbalization of the problem (0.96), inaccurate performance of test (0.83) and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
(13 reference statements)
0
8
0
7
Order By: Relevance
“…Other studies of content validation showed higher, similar or lower number of experts when compared to the number of experts in this search: 120 nurses (nursing diagnosis of anxiety) (11) , 72 experts (nursing diagnosis of spiritual anguish) (12) (13) , 58 experts (nursing diagnosis of nausea) (14) , 50 experts (diagnosis of deficient knowledge) (4) , 32 experts (diagnostic of sexual dysfunction and ineffective sexuality pattern) (15) , 16 experts (diagnostic of fear and anxiety) (16) , 21 experts (nursing interventions for patients with diabetes mellitus) (17) .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Other studies of content validation showed higher, similar or lower number of experts when compared to the number of experts in this search: 120 nurses (nursing diagnosis of anxiety) (11) , 72 experts (nursing diagnosis of spiritual anguish) (12) (13) , 58 experts (nursing diagnosis of nausea) (14) , 50 experts (diagnosis of deficient knowledge) (4) , 32 experts (diagnostic of sexual dysfunction and ineffective sexuality pattern) (15) , 16 experts (diagnostic of fear and anxiety) (16) , 21 experts (nursing interventions for patients with diabetes mellitus) (17) .…”
Section: Discussionmentioning
confidence: 73%
“…The experience in different fields of work is an important characteristic of the expert to the reliability of the results, in a content validation (4) . The identification and use of nursing diagnoses in clinical practice, despite being part of the process of nursing work and being regulated by the Federal Nursing Council Resolutions 272/2002 and 358/2009, although not imposed in many health institutions, as a consolidated activity by professional nurses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As características definidoras selecionadas para este estudo foram adaptadas segundo as definições operacionais de Galdeano, Rossi e Pelegrino: (7) Comportamentos impróprios ou exagerados: paciente assume comportamento inadequado para a situação como rir ou chorar sem parar, gritar, falar demais. Verbalização do problema: paciente verbaliza falta de conhecimento em relação ao seu problema de saúde, em relação aos fatores que desencadearam a doença, e/ou em relação aos procedimentos anestésico-cirúrgicos e/ou em relação ao período pós-operatório.…”
Section: População E Amostra Estudadaunclassified